Effect of Propolis on Bone Quality and Cortical Bone Thickness of Ovariectomized Female Wistar White Rats as A Model for Osteoporosis - Juwita, Dian Ayu; Ahmadin, Almahdy; Rachmaini, Fitri; Abdillah, Rahmad; Fatma, Rosalia Medisa (Pharmaceutical Sciences and Research, 2021)
Estrogen deficiency increases the rate of osteoporosis, especially in menopausal women, by altering the bone tissue microarchitecture. Propolis has compounds that could be used as an alternative therapy to treat estrogen deficiency and to protect against bone damage. This study aims to determine the effect of propolis on bone quality and cortical bone thickness of femoral metaphysis in ovariectomized female Wistar white rats as a model for menopausal osteoporosis. The rats were divided into five groups: negative control group (not subjected to ovariectomy), sham group (subjected to ovariectomy), and treatment groups that were subjected to ovariectomy and given propolis orally at a dose of 180 mg/kg BW, 360 mg/kg BW, and 720 mg/kg BW for 30 days. Bone quality and cortical bone thickness testing were undertaken on the 31st day. The osteoblast and osteoclast cell examination was evaluated using an Olympus BX 51 light microscope at 400x magnification for bone quality and the Betaview program, Beta 3.1MP Sony Exmor CMOS Sensor camera at 40x magnification for cortical bone thickness. Data were analyzed using the one-way ANOVA and continued with Duncan’s multiple range tests. It was found that propolis had a significant effect on the ratio of osteoblast and femur bone osteoclasts (p0.05). The administration of propolis at a dose of 180 mg/kg BW, 360 mg/kg BW, and 720 mg/kg BW had an effect in decreasing the ratio of osteoblasts and metaphysical osteoclast cells of femoral metaphysics. However, propolis administration did not affect the thickness of the femoral metaphysical cortical bone